GAYA HIDUP IBU-IBU DHARMA WANITA PERSATUAN DI KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - ", Mardianah; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the District Kemuning Indragiri Hilir with problems: (1) How Lifestyle Dharma Wanita Persatuan In Behavior Consumption in District Kemuning Indragiri Hilir? (2) What are the Factors Affecting Lifestyle Dharma IFEWanita Persatuan in District Kemuning Indragiri Hilir?. The purpose of this study to Know How Lifestyle background Dharma Wanita Persatuan In Behavior Consumption Patterns in District Kemuning Indragiri Hilir and Factors Affecting Anything Lifestyle Dharma Wanita Persatuan in District Kemuning Indragiri Hilir. This research is quantitative descriptive. The population in this study were who in structured management of Dharma Wanita United in the District Kemuning total 29 people, this population is taken by the census technique re for all the population is used as a sample and using cross tabulation to test indicators into lifestyle changes in this study. To collect data the researcher used questionnaire and documentation. These results indicate that lifestyle Dharma Wanita Untied in Sub District Kemuning caused by factors that affect lifestyle that includes economic, social and cultural patterns of consumption and consists of the consumption of goods, the use of leisure time and use of space, by using cross tables (cross tabulation) based on the processed data is the study had a positive relationship with the proved measurement method.The Keyword : Life Style, dan Dharma Wanita